Ober Funktionen, die keine nullgleiche dividierte Differenz n-ter Ordnung besitzen - Kirjatsky, E. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Кирьяцкий. О функциях, n-я разделенная разность которых не равна нулю E. Kirjackis. Funkcijos, kurių n-tos eilės padalytas skirtumas nėra lygus nuliui